Tinjauan Yuridis Terhadap Bukti Kepemilikan Saham dalam Transaksi Efek Saham Melalui Sekuritas Daring - Luthfiah Hasanah; Abdul Rahman; Rustan Rustan (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to find out and understand how the legal strength of the evidence of investor’s share ownership in online securities that are based on the problem of trading stock securities with the consequences of evidence in the form of electronic accounts, as well as the legal protection that occurs by the Financial Fervices Authority against investors in terms of suspension (stop trading) securities. This thesis research uses normative research type, which uses primary, secondary, and tertiary legal sources. The results of the analysis of this study are the legal strength of proof of share ownership in online stock securities transactions, including the Civil Code, Law Number 8 of 1995 concerning the Capital Market, Law Number 40 of 2007 concerning Limited Liability Companies. Then the role of Financial Fervices Authority in protecting investors in the event of a securities suspension, Financial Fervices Authority taking preventive actions such as socialization and repressive measures such as dispute resolution wherein Article 29 (c) of the Financial Fervices Authority Law states that Financial Fervices Authority in conducting consumer complaints, facilitates the settlement of consumer complaints that are harmed by actors in the Financial Services Institution in accordance with the laws and regulations in the Financial Services sector, carry out regulations, and make the Task Force aware of investments in each region. The suggestion from this researh is that the government should be able to make more specific laws and regulations regarding online stock trading. Abstrak: Penelitian ini bertujuan untuk mengetahui dan memahami bagaimanakah kekuatan hukum bukti kepemilikan saham terhadap investor pada sekuritas daring yang dilatarbelakangi pada permasalahan perdagangan efek saham dengan konsekensi alat bukti yang berbentuk rekening elektronik, serta perlindungan hukum oleh Otoritas Jasa Keuangan (OJK) terhadap investor dalam hal terjadi suspensi (menghentikan perdagangan) sekuritas. Penelitian skripsi ini menggunakan tipe penelitian normatif, yang menggunakan sumber hukum premier, sumber hukum sekunder, dan sumber hukum tersier. Hasil analisis dari penelitian ini ialah kekuatan hukum bukti kepemilikan saham dalam transaksi efek saham secara daring yang diatur dalam berbagai peraturan perundang-undangan antara lain Kitab Undang- Undang Hukum Perdata, Undang-Undang Nomor 8 tahun 1995 tentang Pasar Modal, Undang-Undang Nomor 40 tahun 2007 tentang Perseroan Terbatas. Kemudian peran Otoritas Jasa Keuangan (OJK) dalam perlindungan investor dalam hal terjadi suspensi sekuritas, Otoritas Jasa Keuangan (OJK) melakukan tindakan preventif seperti sosialisasi dan represif seperti penyelesaian sengketa dimana dalam Pasal 29 (c) Undang-Undang Otoritas Jasa Keuangan (OJK) dalam melakukan pengaduan konsumen, memfasilitasi penyelesaian pengaduan konsumen yang dirugikan oleh pelaku di Lembaga Jasa Keuangan, melakukan regulasi, dan membuat satgas waspada investasi pada setiap daerah. Saran dari penelitian ini hendaknya pemerintah dapat membuat peraturan perundang-undangan yang lebih khusus mengenai perdagangan saham secara daring